Research progress in different physical therapies for treating peripheral nerve injuries - Chu, Xiao-Lei; Zhao, Xiao-Xuan; Liu, Shuai-Yi; Li, Ya-Jie; Ding, Ning; Liu, Min-Qi; Li, Qing-Wen; Li, Qi (Frontiers in Neurology, 2025)
Physical therapy is gaining recognition as an effective therapeutic approach in the realm of peripheral nerve injury (PNI) research. This article seeks to provide a comprehensive review of the latest advancements, applications, and mechanisms of action of four physical therapy modalities—ultrasound, electrical stimulation, photobiomodulation, and aerobic exercise—in the context of PNI. Ultrasound, characterized by its mechanical and thermal effects, is widely regarded as an effective non-invasive or minimally invasive method for neural modulation. Electrical stimulation therapy, a prevalent technique in PNI treatment, entails the application of electric currents to stimulate nerve and muscle tissues, thereby facilitating nerve regeneration and mitigating muscle atrophy. Photobiomodulation, a process that influences cell metabolism through the absorption of photon energy, is closely associated with neural regeneration in the field of rehabilitation medicine. Additionally, aerobic exercise, a popular form of physical activity, serves to enhance blood circulation and improve neuronal function. The article discusses various physical therapy methods for peripheral nerve injuries, including hyperbaric oxygen therapy, magnetic therapy, and biofeedback therapy, in addition to traditional approaches. Despite advancements, challenges in nerve injury treatment persist, such as the need for standardized treatment protocols, consideration of individual variations, and assessment of long-term effectiveness. Future research is needed to address these issues. In summary, this article offers theoretical and empirical evidence supporting the utilization of physical therapy in the management of PNI. This research aims to promote further research and clinical practice in this field, contributing to enhancing patient quality of life and recovery outcomes.